Contribution of Islamic Intellectual Organizations to Educational and Social Aspects in Pattani, Thailand - Leengaedayee, Paisul; Riyadi, Agus (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
This research discusses the importance of the contribution of Islamic intellectual organizations to community development in Pattani, Southern Thailand. The main objective of this research is to identify how Islamic intellectual organizations play a role in improving the educational and social fields of the Pattani community. By exploring these dynamics, this article aims to provide deeper insight into how the presence of Islamic intellectuals has influenced community development in Pattani and its relevance in the region's complex social and cultural context. This research uses an ethnographic study approach to explore and understand the role and impact of Islamic intellectual organizations in the context of education and social development in Pattani. The results of this study are that these organizations act as educational centers and places to build solidarity and mutual support among community members.